Animal- versus in vitro-derived antibodies: avoiding the extremes. Issue 1 (1st January 2021) - Bradbury, Andrew R.M.; Dübel, Stefan; Knappik, Achim; Plückthun, Andreas
ABSTRACT: Recent recommendations from the European Union Reference Laboratory regarding the generation of antibodies using animals have stimulated significant debate. Here, four of the scientists who served on the Scientific Advisory Committee provide clarification of their views regarding the use of animals and in vitro platforms in antibody generation. Abbreviations : EURL ECVAM, European Union Reference Laboratory for alternatives to animal testing. ESAC, EURL ECVAM Scientific Advisory Committee